2017
DOI: 10.3390/nu9111184
|View full text |Cite
|
Sign up to set email alerts
|

Skullcap (Scutellaria Baicalensis) Hexane Fraction Inhibits the Permeation of Ovalbumin and Regulates Th1/2 Immune Responses

Abstract: Skullcap (Scutellaria baicalensis) is well known for its anti-inflammatory and anti-allergic effects. In our previous study, we found that skullcap could inhibit allergen permeation and regulate Th1/2 immune balance. To reveal the key fractions and components of skullcap, we fractionated skullcap extract into five fractions: hexane, chloroform, ethyl acetate, butanol, and water fraction. Among these fractions, the hexane fraction significantly suppressed the production of Th2-mediated cytokines (Interleukin (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…Results revealed that baicalein (47) was able to increase Treg cells population through induction of CD4 + FOXP 3 + T cell differentiation without causing any cytotoxicity at concentrations smaller than 10 µmol/L (Bae et al, 2016). In light of a study by Jung et al (2017), linoleic acid (50) in hexane fraction from ethanol extract of S. baicalensis roots was reported to cause a significant suppression (P < 0.05) in the production of pro-allergic cytokines (IL-4, IL-5, IL-10 and IL-13) and enhancement of secretion of T H 1 cytokines (IFN-γ (P < 0.05) and IL-12 (P < 0.01)). The fact that a fatty acid from a plant can contribute anti-allergic effect through restoration of T H 1/T H 2 balance is a new discovery (Jung et al, 2017).…”
Section: Regulation Of T Cell Responsesmentioning
confidence: 98%
See 1 more Smart Citation
“…Results revealed that baicalein (47) was able to increase Treg cells population through induction of CD4 + FOXP 3 + T cell differentiation without causing any cytotoxicity at concentrations smaller than 10 µmol/L (Bae et al, 2016). In light of a study by Jung et al (2017), linoleic acid (50) in hexane fraction from ethanol extract of S. baicalensis roots was reported to cause a significant suppression (P < 0.05) in the production of pro-allergic cytokines (IL-4, IL-5, IL-10 and IL-13) and enhancement of secretion of T H 1 cytokines (IFN-γ (P < 0.05) and IL-12 (P < 0.01)). The fact that a fatty acid from a plant can contribute anti-allergic effect through restoration of T H 1/T H 2 balance is a new discovery (Jung et al, 2017).…”
Section: Regulation Of T Cell Responsesmentioning
confidence: 98%
“…In light of a study by Jung et al (2017), linoleic acid (50) in hexane fraction from ethanol extract of S. baicalensis roots was reported to cause a significant suppression (P < 0.05) in the production of pro-allergic cytokines (IL-4, IL-5, IL-10 and IL-13) and enhancement of secretion of T H 1 cytokines (IFN-γ (P < 0.05) and IL-12 (P < 0.01)). The fact that a fatty acid from a plant can contribute anti-allergic effect through restoration of T H 1/T H 2 balance is a new discovery (Jung et al, 2017). A similar outcome was noted in a food allergy murine model conducted by Shin et al (2014b) with S. baicalensis ethanol extract.…”
Section: Regulation Of T Cell Responsesmentioning
confidence: 98%
“… Skullcap 70% Ethanol Polyphenolic compounds (baicalin, baicalein and wogonin) Treatment for allergic, inflammation and viral infections. Jung et al; 57 Li-Weber; 131 Zhang et al 132 S. ternatum Ophioglossaceae It is a common herb and is mainly found in China. Whole plant 70% Ethanol Not identified Deemed to have anti-toxic effects in the body.…”
Section: Anti-asthmatic Potential Of Tmps Against Ova-induced Asthma In Animalsmentioning
confidence: 99%
“…In a study, n-hexane fraction of 70% Scutellaria baicalensis ( S. baicalensis ) ethanolic extract has significantly suppressed the production of Th2-mediated cytokines and increased Th1-mediated cytokines against OVA-induced animals. 57 The 70% aqueous ethanolic extract of Sceptridium ternatum ( S. ternatum ) treatment significantly reduced AHR, raised the ratio of Th1/Th2 and reduced Cyslt1 mRNA level in a dose-dependent manner. 58 Moreover, high-dose of S. ternatum had similar efficacy as the investigated standard drug (Montelukast) in a mouse asthma model and therefore is a good potential anti-asthmatic agent.…”
Section: Anti-asthmatic Potential Of Tmps Against Ova-induced Asthma In Animalsmentioning
confidence: 99%
See 1 more Smart Citation